Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 4977 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Emberiza cioides J.F.Brandt, 1843" ] } The dataset includes 4977 records from 76 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001282-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences